PENGUKURAN DAN ANALISIS DOSIS PROTEKSI RADIASI SINAR-X DI UNIT RADIOLOGI RS. IBNU SINA YW-UMI - Rahmayani, Rai; Sahara, Sahara; Zelviani, Sri (Universitas Islam Negeri Alauddin Makassar, 2020)
This study aims to determine the dose of radiation in a large room with measurements from various directions, knowing the great wall by measuring the absorption of a scattering outdoors doses, and determine the radiation dose received by radiation workers in radiology installations. This study uses Surveymeter, the meter, the best ruler X-rays, and phantom. In measurements carried out three phases: the first measure exposure dose in a room with a distance of 1 m and 2 m with a voltage of 50 kV, 55 kV and 60 kV, the second stage taking the raw data of radiation received by workers of the head of the installation and the third stage knowing absorption wall by measuring the scattering dose outdoors. Based on the research that has been done, it can be concluded that the largest radiation dose is on the right side of the tube either with an object that is 33 ÂµSv/h or without an object that is 33.6 ÂµSv/h at a distance of 1 m and a voltage of 60 kV, but the value at both the other positions, namely the left and front side of the plane do not have such a large difference that it can be stated that the values obtained at the three positions are almost the same at the same voltage and distance, the largest dose received by operator IV is 0.215 mSv/h and the average dose the average received by workers is 0.2 mSv/h in accordance with Regulation of BAPETEN No.4 of 2013, and the ability of the walls to absorb outdoor radiation doses is very good as seen from the results of undetectable radiation measurements because all are absorbed by the wall. Â